Pengaruh Sari Jahe Gajah (Zingiber Officinale Rosc.) Terhadap Organ Dalam (Giblet) Burung Puyuh (Coturnix Coturnix Japonica) - Mustofa Kamal Khoerudin; Jeki M.W. Wibawanti; Rinawidiastuti Rinawidiastuti (Jurnal Riset Agribisnis dan Peternakan, 2019)
This study aims to determine the effect of elephant ginger (Zingiber officinale Rosc.) Juice on the percentage of carcasses, quail organs. The study was conducted at the Field Laboratory of Animal Husbandry Study Program, Muhammadiyah University Purworejo. The research material used was 120 quail (Coturnix-coturnix Japonica) aged 3 weeks, ginger juice, and commercial feed. The tools used include cages to keep quails the size of each box is 39 cm, length 50 cm, and width 40 cm, feed and beverage containers, digital scales. The treatment provided in this study used a Completely Randomized Design (CRD) consisting of 6 treatments and 4 replications. The care given is the level of ginger juice which is 0; 5; 10; 15; 20; 25% of the total commercial feed provided. The parameters observed were internal organs (giblets). The results of ginger juice supplement mixed with drinking water showed that the percentage of the liver did not have a significant effect (P> 0.05) with an amount of 2.72; 2,81; 2.91; 2.97; 2.76; and 2.91%. The percentage of heart has no significant effect (P> 0.05) of 0.75; 0.66; 0.79; 0.75; 0.79; and 0.75%. The percentage of gizzard has no significant effect (P> 0.05) with a total of 1.27; 1.19; 1,11; 1,11; 1.17; and 1.08%. Based on the results of the study it can be concluded that the administration of elephant ginger extract (Zingiber Officinale Rosc.) In drinking water up to the level of 25% has no significant effect on quail and internal organs (giblets).